A randomised control trial assessing the impact of an investment based intervention on weight-loss, beliefs and behaviour after bariatric surgery: study protocol - Hollywood, Amelia (BMC Obes, 2015)
BACKGROUND: Although obesity surgery is currently the most effective method for achieving weight loss, not all patients lose the desired amount of weight and some show weight regain. Previous research shows that successful weight loss may be associated with the amount of investment the patient feels that they have made in their operation. For example, those who feel that it has taken more time and effort to organise, has cost more money, has been more disruptive to their lives and has caused pain are more likely to lose weight after their operation. Therefore, it seems as if the greater the sense of investment, the greater the motivation to make the operation a success. The present study aims to build on these findings by encouraging weight loss surgery patients to focus on the investment they have made, thus making their investment more salient to them and a means to improve weight loss outcomes. METHODS: The study involves an open randomised parallel group control trial with patients allocated either to the control or investment intervention group. Using third party blinded randomization, half the patients will be asked to rate and describe the investment they have made in their operation just before surgery then 3 and 6 months after surgery. All patients will record their weight, beliefs about food, intentions to change and actual eating and exercise behaviour at baseline then 3, 6 and 12 months follow up. Patients will be recruited from the bariatric surgery pre-assessment clinic at University College Hospital, London. The primary outcome is to explore the impact of the investment based intervention on patient’s weight and BMI, with secondary outcomes of patients’ beliefs about foods, behavioural intentions and diet and exercise behaviours. DISCUSSION: It is predicted that the investment intervention will improve excess weight loss post-surgery, together with beliefs about food, intentions to change and actual change in diet and exercise behaviour. This has cost implications for the NHS and other healthcare providers as improved effectiveness of bariatric surgery reduces the health costs of obese patients in the longer term and this simple, easy to administer and low cost intervention could become routine practice for bariatric patients. TRIAL REGISTRATION: ClinicalTrials.gov identifier NCT02045628; December 2, 2013.